In Search of a Problem: Mapping Controversies over NHS (England) Patient Data with Digital Tools. (May 2019) - Moats, David; McFall, Liz
There is a long history in science and technology studies (STS) of tracking problematic objects, such as controversies, matters of concern, and issues, using various digital tools. But what happens when public problems do not play out in these familiar ways? In this paper, we will think through the methodological implications of studying "problems" in relation to recent events surrounding the sharing of patient data in the National Health Service in the United Kingdom. When a data sharing agreement called care.data was announced in 2013, nearly 1.5 million citizens chose to opt out. Yet, in subsequent years, there has been little evidence of a robust public mobilising around data sharing. We will attempt to track this elusive 'non problem' using some digital tools developed in STS for the purpose of mapping issues and problem definitions within science. Although we find these digital tools are unable to capture the "problem, " the process of searching helps us map the terrain of the case and forces us to consider wider definitions.